Work Roll Cooling System Design Optimisation in Presence of Uncertainty - Azene, Y. T.; Roy, Rajkumar; Farrugia, Didier; Onisa, C.; Mehnen, Jorn; Trautmann, H. (Cranfield University Press, 2009)
The paper presents a framework to optimise the design of work roll based on the cooling performance. The framework develops Meta models from a set of Finite Element Analysis (FEA) of the roll cooling. A design of experiment technique is used to identify the FEA runs. The research also identifies sources of uncertainties in the design process. A robust evolutionary multi-objective algorithm is applied to the design optimisation I order to identify a set of good solutions in the presence of uncertainties both in the decision and objective spaces.
Organised by: Cranfield University
Keywords: Roll cooling design; Uncertainty; Design optimisation; Multi-objective optimisation